Permeability reduction in porous media due to suspended particles - Vagharfard, Hassan, author; Grigg, Neil, advisor; Durnford, Deanna, advisor; Albertson, M. L., committee member; Zachmann, D. W., committee member (Colorado State University. Libraries, 2001)
Artificial recharge is a promising method for replacing water that is being withdrawn from aquifers. Although there are several water sources available, reclaimed agricultural, municipal and industrial wastewaters appear to be the water of choice for injecting into the underground reservoir. Frequently, the recharge capacity of wells decreases with time due to reductions in hydraulic conductivity of the aquifer material by suspended particles, eventually clogging the aquifer. Clogging is the retention of fine particles in a geological formation. This process causes a reduction in pore space, which reduces the aquifer's capacity to store and transmit water. The purpose of this study was to analyze the reduction of hydraulic conductivity in porous media due to retention of fine particles. To meet the objective of this study, laboratory experiments were conducted. First relationships between hydraulic conductivity, porosity, and density of the porous media with respect to concentration of the particles in suspension were developed, using a constant head permeameter. Separately, a column test experiment was conducted. The sand column was packed homogeneously and a solution containing carbon fines was injected into the column. The water pressure head along the column and outflow were measured during the experiment. The changes in physical and hydraulic properties of the sand were calculated and compared with saturated soil properties at the start of the column test experiment. The results show that most of the carbon was captured in the first centimeter of the soil (69%) and hydraulic conductivity in this region was reduced up to 99%. About 98% of the total carbon injected into the column was entrapped in the first three centimeters and no carbon could be detected after six centimeters of the sand column. A numerical model was developed to solve the flow and transport equations and predict the clogging process seen in the column test experiment. This model used empirical equations developed from the laboratory experiments that relate concentration of the fine particles in suspension to physical and hydraulic properties of the porous media. Results from this study show that clogging of the porous media by fine particles is a nonlinear process but one that can be predicted by numerical modeling.
Keywords: civil engineering